Implementation of information technology on the publication and promotion of mangrove eco-tourism in Sisarahili, Teluk Siabang village - Nababan, Esther Sorta Mauli; Siahaan, Nelson Manumpak; Harahap, Agus Salim; Sembiring, Pramio Garson; Ziliwu, Meyman Sokhi (Talenta Publisher, 2020)
The mangrove forests that stretch along the coast of the Nias islands have great potential to improve the economy of the surrounding communities. One of the largest and most extensive mangrove areas is in Ba'a bay, located in Sisarahili bay, Siabang village, Sawo District, North Nias Regency. Mangrove forest turns out to be a natural resource and tourism potential that is crowded with visitors, supported by its existence in a wide stretch of coastline. However, the development of tourism potential still needs to be done to further increase the arrival of both domestic and foreign tourists. Several things have been done to support increased publication and promotion by increasing the human resources of tourism awareness groups through training and workshops, improving facilities and infrastructure, transportation and accommodation and also the application of information technology media to maximize publication and promotion, so that visitors are not only local people but also from outside the region. The use of page-based information technology and social media as media is implemented to support publication and promotion in accordance with the results of a survey conducted by the community service team for visitors who come. As many as 65% of visitors get information about mangrove tourism in Teluk ba'a from printed social media and 15% from websites / pages, while 20% get information from friends, online newspapers and communities around the mangrove tourism environment.